The impact of Financing of Syariah Bank toward the performance and Welfare of Small Medium Enterprise - Faisol, Faisol (Universitas Nusantara PGRI Kediri, 2018)
The purpose of this paper is to examine empirically the influence financing of Syariah Bank toward the business performance, the influence of financing of syariah bank toward welfare of small entrepreneurs, and the influence of performance of UKM toward the welfare of small entrepreneurs. The population of this research is all of the small medium enterprises in the District of Kediri who got Islamic bank financing for one year. These samples included 71 SMEs agribusiness. Sampling was done by purposive sampling research, namely SME agribusiness got Islamic bank financing for one year, with a workforce of 5 to 19 people. Questionnaire was used as a tool to collect primary data. The method of analysis used partial least square (PLS). Testing is done with a structural model (Inner model) and models of measurement (Outer model) Statistically, the results show that the Islamic bank financing significant influence with a positive direction on the performance of SMEs, this means that when the Islamic bank financing improved, will improve the performance of SMEs, further financing Islamic banks have a significant effect with positive direction towards the well-being of SMEs so that when the Islamic bank financing improved well-being of SMEs will be increased then the performance of SMEs have significant influence in a positive direction for the welfare of SMEs. So if the business performance of SMEs improved, well-being will increase.